PD-1-Mediated PI3K/Akt/mTOR, Caspase 9/Caspase 3 and ERK Pathways Are Involved in Regulating the Apoptosis and Proliferation of CD4+ and CD8+ T Cells During BVDV Infection in vitro - Liu, Yu; Liu, Shanshan; Wu, Chenhua; Huang, Wenjing; Xu, Bin; Lian, Shuai; Wang, Li; Yue, Shan; Chen, Nannan; Zhu, Zhanbo (Frontiers in Immunology, 2020)
Acute infection of bovine viral diarrhea virus (BVDV) is associated with immune dysfunction and can cause peripheral blood lymphopenia and lymphocyte apoptosis. Our previous study has confirmed that programmed death-1 (PD-1) blockade inhibits peripheral blood lymphocyte (PBL) apoptosis and restores proliferation and anti-viral immune functions of lymphocytes after BVDV infection in vitro. However, the immunomodulatory effects of PD-1 pathway on major PBL subsets are unclear and their underlying molecular mechanisms need to be further studied. Therefore, in this study, we examined PD-1 expression in bovine PBL subsets after BVDV infection in vitro and analyzed the effects of PD-1 blockade on the apoptosis and proliferation of CD4+ and CD8+ T cells and expression of PD-1 downstream signaling molecules. The results showed that PD-1 expression was enhanced on CD4+ and CD8+ T cells, but not on CD21+ B cells after cytopathic (CP) BVDV (strain NADL) and non-cytopathic (NCP) BVDV (strain KD) infection in vitro and PD-1 blockade significantly reduced the apoptosis of CD4+ and CD8+ T cells after these two strains infection. Remarkably, PD-1 blockade significantly increased the proliferation of CD4+ and CD8+ T cells after NADL strain infection, but only significantly increased the proliferation of CD4+ T cells after KD strain infection. In addition, we confirmed the involvement of PI3K/Akt/mTOR, ERK and caspase 9/caspase 3 pathways in NADL strain induction of apoptosis and inhibition of CD4+ and CD8+ T cell proliferation. These pathways were shown to have a similar effect on CD4+ T cells following KD strain infection. Remarkably, PD-1 blockade in KD strain infected cells did not significantly affect proliferation and p-mTOR and p-ERK levels of CD8+ T cells. Our results confirm that PD-1-mediated PI3K/Akt/mTOR, caspase 9/caspase 3 and ERK pathways are involved in regulating the apoptosis and proliferation of CD4+ and CD8+ T cells during BVDV infection in vitro. Notably, ERK is involved in the regulation mechanism PD-1 mediated only when the cells are infected with CP BVDV. Our findings provide a scientific basis for exploring the molecular mechanism of immune dysfunction caused by acute BVDV infection.